Faktor-Faktor yang Memengaruhi Masyarakat Kota Yogyakarta Untuk Berjalan Kaki di Jalur Pedestrian Pasca Penataan Ulang (Kasus: Jl. Jenderal Sudirman, Kota Yogyakarta) - Novianto, Naufal Ferdian; Hidayati, Isti (FSTPT Indonesia, 2024)
Yogyakarta has been focusing its development towards a walkable city through pedestrian improvement projects implemented on Jenderal Sudirman Street. However, the pedestrian improvement project cannot increase pedestrian activity three years after its completion. Therefore, this research aims to identify the factors that influence the willingness of Yogyakarta inhabitants to use the pedestrian paths on Jenderal Sudirman Street after the improvement project. The analysis used a deductive quantitative approach, i.e., binary logistic regression of 150 questionnaires collected through convenience sampling. The study shows that providing lighting, shade, parking lots, and pedestrian path continuity significantly affects walking activities after the improvement project. Moreover, gender